2017
DOI: 10.1016/j.aorn.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Unplanned Perioperative Hypothermia in Children

Abstract: Unplanned perioperative hypothermia is a common surgical risk. Unplanned hypothermia is defined as a body temperature below 36° C (96.8° F) during any phase of the perioperative period. Perioperative nurses at a Midwestern tertiary pediatric hospital developed an evidence-based clinical practice guideline (CPG) designed to maintain normothermia for the pediatric surgical population. This CPG outlined standard thermoregulation nursing interventions and required the consistent use of a temporal artery thermomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(63 reference statements)
0
8
1
Order By: Relevance
“…The generally suggested operating room temperature is 20-23.9°C, but it is around 23-24°C for pediatric cases (2,8). This value was maintained for all operations performed in this study.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The generally suggested operating room temperature is 20-23.9°C, but it is around 23-24°C for pediatric cases (2,8). This value was maintained for all operations performed in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Beedle et al (8) have found the incidence of pediatric perioperative hyperthermia to be 16.3% and that this rate can fall to 1.84% with an attentive perioperative care (that is based on the guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent temperature monitoring coupled with standardized interventions (e.g., warming blankets) reduced unplanned hypothermia incidence from 16 percent to 1.8 percent (Level III Evidence). 41…”
Section: Resultsmentioning
confidence: 99%
“…Two large studies reported relatively high rates of PH in the pediatric surgical population: Beedle et al documented a PH rate of approximately 20% in 1504 patients, and Pearce et al reported a rate of PH of 53% on 530 pediatric patients. 1,19 Although Kim et al found that only 6% of pediatric neurosurgery patients were hypothermic on arrival to the postanesthesia care unit (PACU), this is misleading because patients are least likely to be hypothermic at the end of a case given that standard operating room (OR) care involves a forced air warmer (FAW) and operative draping provides a good deal of insulation. 14 Not only are patients at significant risk, but current OR culture may not even prioritize a workflow fostering perioperative normothermia: a Europe-wide survey indicated that a mere 40% of patients were warmed intraoperatively and temperature was measured in only 20% of cases.…”
Section: Mutchnick Et Almentioning
confidence: 99%